2010
DOI: 10.1007/s00405-010-1424-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR-4 and TNF-alpha polymorphisms with clinical symptoms and cytokine levels in patients with allergic rhinitis

Abstract: Our objective was to determine the frequency of TNF-alpha -238, -308 G/A promoter and TLR-4 299 D/G and 399 T/I polymorphisms in healthy population and in patients with seasonal allergic rhinitis, and to examine its influences on serum TNF-alpha, TNF receptor-1, Fas, Fas-ligand, IgE levels and on clinical symptoms. A pilot study was performed in 66 patients with seasonal allergic rhinitis to ragweed pollen and 161 non-allergic subjects using PCR-RFLP technique and ELISA. Carriers of the -238A and -308G alleles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…However, there were very few carriers of this polymorphism (10 subjects), which limits the interpretation of the significance of this polymorphism in our study sample. Previous studies on the Caucasian population found that the TNFα -238G>A polymorphism was associated with an increased risk for asthma [22,40] and allergic rhinitis [41], while no significant association was found with atopic dermatitis [14,42,43]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there were very few carriers of this polymorphism (10 subjects), which limits the interpretation of the significance of this polymorphism in our study sample. Previous studies on the Caucasian population found that the TNFα -238G>A polymorphism was associated with an increased risk for asthma [22,40] and allergic rhinitis [41], while no significant association was found with atopic dermatitis [14,42,43]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be speculated that in atopic dermatitis a part of the pathogenesis is related to defective TNFα production and activity in the skin, which is promoted with the TNFα -308GG genotype. Additionally, the TNFα -308G>A polymorphism was found to be positively associated with serum TNFα levels, but negatively with nasal TNFα levels [34,41]. It will be of interest to further study the association of TNFα -308 genotypes with TNFα levels in the skin, respiratory mucosa and blood of atopic and nonatopic subjects, keeping in mind the already revealed discrepancy in the influence of TNFα polymorphisms on serum TNFα levels and local TNFα levels in nasal mucosa, as well as generally diminished TNFα levels in the immune cells of patients with atopic dermatitis [69,70,71,72].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it has been observed that polymorphisms in human TLR promoters may result in deficiency in TLR signaling, increasing or decreasing the susceptibility to infectious disease (Ragnarsdóttir et al, 2010;Krasznai et al, 2011). In pigs, a total of 40 single-nucleotide polymorphisms (SNPs) have been reported in the TLR5 coding sequence (Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%